(untitled) (Nuntius Antiquus, 2010)
We intend to relate Plutarch and Foucault through a character present in the work of both thinkers, namely, Alcibiades, the eugenés. A comparison between the two representations shows that the focus of interest differs in each case. Our reflection is based on the following questions: Why doesn’t Foucault discuss Plutarch’s Alcibiades in The Hermeneutics of the Subject? Would it be because, unlike Plato, the Greek moralist reveals the aristocrat as a failure, as the result of a mistaken pedagogical choice or as the portrait of his community?